Impact of anaerobic exercise integrated into regular training on experienced judo athletes: running vs. repetitive throws - Kamandulis, S.; Dudeniene, L.; Snieckus, A.; Kniubaite, A.; Mickevicius, M.; Lukonaitiene, I.; Venckunas, T.; Stasiule, L.; Stasiulis, A. (The Journal of Strength and Conditioning Research, 2024)
Anaerobic training in high-level athletes is of considerable interest to practitioners aiming to optimize performance. This study compared the impact of interval anaerobic training (IAT) sessions consisting of either high-intensity running or throwing that were performed twice a week together with regular judo training on the anaerobic and aerobic performance of experienced judo athletes. Employing a repeated-measures, counterbalancing, research design, 12 national team judo athletes (7 women and 5 men; mean age, 20.4 ± 0.95 years; mean judo training experience, 13.4 ± 1.4 years; competitive level, black belt first and second Dan) performed each IAT modality for 6 weeks, for a full training cycle of 12 weeks. Assessments of their anaerobic fitness (Cunningham and Faulkner Anaerobic Treadmill Test), sport-specific anaerobic fitness (Special Judo Fitness Test [SJFT]), and aerobic capacity (maximal incremental treadmill running test) were performed before, after 6 weeks, and after 12 weeks of training. The uphill running performance improved by 13.1% over the 12-week period (p = 0.047). Simultaneously, there was a 9.0% improvement in the SJFT index and a 6.9% increase in the number of throws (p = 0.011 and p = 0.017, respectively). Although a trend for throwing drills being more effective than interval sprint running was observed, the interaction effect lacked statistical significance (p = 0.074). Moreover, no substantial changes were noted in aerobic endurance markers. In conclusion, this study suggests that incorporating specific and nonspecific high-intensity drills into a routine training regimen may enhance anaerobic capacity among well-trained judo athletes, potentially leading to favorable competitive outcomes.